Experiences of Pre‐Implantation Genetic Diagnosis (PGD) in Sweden: a Three‐Year Follow‐Up of Men and Women. Issue 5 (12th February 2017) - Järvholm, Stina; Thurin‐Kjellberg, Ann; Broberg, Malin
Abstract: Men and women with a hereditary genetic disease are faced with different options when they wish to become parents. One is pre‐implantation genetic diagnosis (PGD) which is a combination of in vitro fertilization (IVF) and genetic analysis of the embryo before implantation. The present study focused on men and women's psychological experiences of PGD three years after applying for PGD. Nineteen women and seventeen men (i.e. seventeen couples and two women) participated. The interviews were analysed by thematic method. It is better to have tried was identified as a master theme, under which came three underlying sub‐themes, which had the following headings: Practical experience of PGD, Psychological experience of PGD and Goals of PGD. The results show that men and women three years after PGD are still psychologically affected by their experience. The men and women raised concerns that their relationship had been affected, both positively and negatively, and feelings of anxiety and depression still remained. Healthcare services should recognize the heterogeneous nature of the group being studied and therefore the need for counselling can arise at different times and in relation to different areas, regardless of the outcome of the PGD.